Clinical Profile and Outcome of Neonates Admitted to the Neonatal Care Unit at Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet (Jalalabad Medical Journal, 2025)
The neonatal mortality rate is still high in Bangladesh. It is crucial to identify areas where health care can be enhanced in order to improve newborn outcomes. The objective of this study was to describe the reasons for admission and the magnitude of neonatal mortality in the neonatal care unit of Jalalabad Ragib-Rabeya Medical College Hospital. This cross-sectional study was conducted between the periods of 1st January 2018 and 30th June 2018. Data were collected from the inpatient record files at the hospital record section. A total of 854 patients were included in the study. Among them, males were 57.4% and 42.6% were females. Most of the admitted neonates (78.7%) were inborn. Prematurity was present in 23.6% of neonates. The majority of the neonates (76.4%) were admitted within 24 hours of birth. The most common reasons for neonatal admission were low birth weight (44.8%), neonatal sepsis (42.6%), asphyxia (40.6%), neonatal jaundice (24.8%), hypoxic-ischemic encephalopathy (10.7%), congenital anomaly (8.1%), and infants of diabetic mothers (5%). The overall death rate was 11%. Sepsis (60.6%), LBW (59.6%), asphyxia (55.3%), and prematurity (51.1%) were the main contributors to neonatal death. Prematurity, birth weight